DETERMINASI MODEL RESOLUSI KONFLIK TERHADAP PRESTASI BELAJAR AGAMA HINDU DENGAN KOVARIABEL SIKAP MULTIKULTUR DAN EFIKASI DIRI PADA MAHASISWA PGSD STAHN MPU KUTURAN SINGARAJA - Ni Nyoman Lisna Handayani; Ni Ketut Erna Muliastrini; I Putu Suardipa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This research aims to examine the influence of conflict resolution teaching model towards Hindu Religious’s academic achievement with multicultural attitude and self-efficacy covariable. This quantitative research study was conducted to students of PGSD department in Ganesha University of education using experiment method with Single Factor independent groups design with use of covariate and involved 67 students. Data were analyzed with covariance analysis (ANACOVA). The result this research study shows: 1) there are differences in Hindu Religious’s academic achievement between students who involved in conflict resolution model learning with students who involved in conventional learning. 2) There are differences in Hindu Religious’s academic achievement between students who involved in conflict resolution model learning with students who involved in conventional learning by controlling multicultural attitude. 3) There are differences in Hindu Religious’s academic achievement between students who involved in conflict resolution model learning with students who involved in conventional learning by controlling self-efficacy. 4) There are differences in Hindu Religious’s academic achievement between students who involved in conflict resolution model learning with students who involved in conventional learning by controlling multicultural attitude and self-efficacy simultaneously.